The Role of Glocalization Strategies in Enhancing the Global Reach of Javanese Pop Music - Narayanasandhy, I Wayan M. Dhamma; Sembiring, Murpin Josua; Kodrat, David Sukardi (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2026)
Javanese Pop Music holds substantial potential for global recognition; however, its international reach remains limited due to the absence of well-structured glocalization strategies. This study aims to evaluate the effectiveness of cross-cultural adaptation, digital streaming platforms, international collaboration, and fan community engagement in promoting the globalization of Javanese Pop Music. A quantitative approach was employed through a survey of 100 music industry practitioners, with data analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) across nine variables measured by 39 indicators. The findings reveal that cross-cultural adaptation and the use of music streaming platforms do not exert significant direct effects on the globalization of Javanese Pop Music, but have significant indirect effects through brand image and fan engagement. In contrast, fan communities and international collaboration demonstrate positive and significant direct influences on global reach. The limited moderating roles of market orientation and local government support further indicate that the globalization of Javanese Pop Music is shaped more strongly by relational and participatory mechanisms, particularly brand image development, sustained fan engagement, and cross-national collaboration networks, than by cultural adaptation or digital access alone. Accordingly, this study provides empirical evidence that the globalization of Javanese Pop Music can be strengthened through stronger brand image formation, sustained fan engagement, and adaptive cross-national collaboration within an evolving digital music ecosystem.